PENGARUH PENGGUNAAN GITHUB DAN EDUTRACK TERHADAP MOTIVASI MAHASISWA DALAM PROYEK PERANGKAT LUNAK - Muhammad Riansyah Tohamba; LM Bahtiar Aksara (Program Studi Ilmu Komputer FMIPA-UHO, 2025)
The integration of digital technologies in education continues to advance, including the use of GitHub as a collaboration platform and EduTrack as a progress monitoring tool. This study aims to evaluate the impact of GitHub and EduTrack on students’ motivation during software project development. A total of 104 students participated in this study, utilizing GitHub for team project management and EduTrack for periodic progress evaluation. Data were collected through a Likert-scale questionnaire designed to measure autonomy, competence, relatedness, and industry readiness. Statistical analysis using the t-test revealed that several dimensions of students’ motivation were significantly influenced by the use of these platforms. The findings provide new insights into the integration of digital tools to support collaborative learning and prepare students for industry challenges.